2022
DOI: 10.1371/journal.pone.0269539
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of the emergency nurses’ professional resilience tool

Abstract: Background There is no specific tool for measuring the professional resilience of emergency nurses. Therefore, the present study aimed to design and psychometrically evaluate a new tool named the emergency nurses’ professional resilience tool. Method This mixed-method sequential exploratory study was conducted in two phases: (1) item generation using literature review and evaluation of the results of a qualitative study and (2) psychometric evaluation of the developed scale. The face, content, and construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Further, we compiled the instrument revised by experts into a questionnaire and randomly sampled 1,286 CDC emergency responders in Shanghai, using the questionnaires they filled in for reliability and validity analyses. Additional, reliability and structural validity were examined using Cronbach’s α coefficient and exploratory factor analysis, respectively, which are widely used in the development and validation of instruments ( 9 , 28 ). The results of this study showed that all the Cronbach’s α coefficients were above 0.85, and the factor loadings in exploratory factor analysis were above 0.65, and there were no double loadings, indicating good results for reliability and validity validation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, we compiled the instrument revised by experts into a questionnaire and randomly sampled 1,286 CDC emergency responders in Shanghai, using the questionnaires they filled in for reliability and validity analyses. Additional, reliability and structural validity were examined using Cronbach’s α coefficient and exploratory factor analysis, respectively, which are widely used in the development and validation of instruments ( 9 , 28 ). The results of this study showed that all the Cronbach’s α coefficients were above 0.85, and the factor loadings in exploratory factor analysis were above 0.65, and there were no double loadings, indicating good results for reliability and validity validation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering the limitations of the trait and outcome perspectives, in this study, we developed the career resilience measurement instrument from a process perspective, describing protective individual characteristics, internal and external interactions and self-regulatory processes, and adaptive outcomes and employing a variable-centered approach to reveal the dynamic process of an individual’s breakdown from equilibrium to reintegration into equilibrium. In addition, career resilience in the healthcare field has mostly been studied with nurses, and primary healthcare professionals ( 28 , 33–37 ), while basically, no studies are available regarding CDC emergency responders. This study introduces career resilience to the group of CDC emergency responders in hopes of focusing on the mental health and work status of this group, so that they can better respond to public health emergencies and protect public health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation